Electromigration Failure Prediction and Reliability Evaluation of Solder Bumps for FCBGA package - ZHANG, Yuanxiang (Engineering Transactions, 2015)
Electromigration (EM) in solder joints under high current density has become a critical reliability issue for the future high density microelectronic packaging. A practical method of atomic density integral (ADI) for predicting solder bump electromigration reliability is proposed in this paper. The driving forces in electromigration include electron wind force, stress gradient, temperature gradient as well as atomic density gradient. The electromigration simulation is performed on flip chip ball grid array (FCBGA) package based on ADI method, and the simulation results for void generation and time to failure (TTF) have a reasonably good correlation with the testing results. Orthogonal experimental design has been used to evaluate the effect of design parameters on TTF of electromigration. Based on this study, some practical recommendations are made to optimize the package design and improve the solder bump electromigration reliability.